If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6xsquare + -37x = -6 Solving 6aeqrsux + -37x = -6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '37x' to each side of the equation. 6aeqrsux + -37x + 37x = -6 + 37x Combine like terms: -37x + 37x = 0 6aeqrsux + 0 = -6 + 37x 6aeqrsux = -6 + 37x Divide each side by '6eqrsux'. a = -1e-1q-1r-1s-1u-1x-1 + 6.166666667e-1q-1r-1s-1u-1 Simplifying a = -1e-1q-1r-1s-1u-1x-1 + 6.166666667e-1q-1r-1s-1u-1 Reorder the terms: a = 6.166666667e-1q-1r-1s-1u-1 + -1e-1q-1r-1s-1u-1x-1
| 20m-14=10 | | 2(4+3m)=3 | | 2,5(x-2)-1,5x=1 | | 3(k+5)=-8 | | (X-4)=15 | | 6=(1/2)(5)(x) | | 2m+18=6m | | -5(10+2x)-2(x+4)=14 | | 9=8*-5+8 | | 2y/3-8=2y+3 | | -9(5-4x)-(3x+5)=49 | | 2(m+4)=6 | | -4(10-8y)=24 | | k/2-4=-7 | | 5(x+2)=4(x-6) | | 2x^(3/2)=250 | | 7x^8-7=0 | | 2(7-w)-4=0 | | -6=b/5-10 | | 2x^3/2=250 | | 2g-4=10h | | 3=-b-6 | | 9+x/4=5 | | 5x-4-2x+3=-7-3x+5+2x | | -160=2-9x | | -7x+3=-4 | | 6=1+5(y-2) | | 5x+8=4x-1 | | 5m-2(m-5)=-17 | | -8+6n=82 | | -2p^2q^3=0 | | 14-1/3x-2 |